2017
DOI: 10.1007/s10856-017-5898-3
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and biological characteristics of BMP-2/IGF-1-loaded three-dimensional coaxial electrospun fibrous membranes for bone defect repair

Abstract: Coaxial electrospun fibrous membranes show favorable mechanical properties for use in guided bone regeneration (GBR). We used coaxial electrospinning technology to fabricate three-dimensional nanofiber membranes loaded with BMP-2 and IGF-1, and assessed the physicochemical and biological properties of these novel membranes in vitro. We fabricated four experimental groups of BMP-2/IGF-1/BSA-loaded membranes with different flow ratios (shell/core). Membrane characteristics were assessed by scanning and transmiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 73 publications
1
21
0
Order By: Relevance
“…BSA was a stabilizer in the system. The release result of the nanofibers showed that nanofibers with higher shell flow ratio released BMP2, IGF1, and BSA more slowly in 3 days and in a more sustained manner up to 28 days of release [87]. Similar studies evaluated the release of BSA and NGF [9], BSA and tetrapeptide val-gal-pro-gly [88], and antibiotics (vancomycin and ceftazidime) and BMP2 from core-shell nanofibers [89].…”
Section: Delivery Of Multiple Drug and Biomolecules From Core-shell Nmentioning
confidence: 83%
See 1 more Smart Citation
“…BSA was a stabilizer in the system. The release result of the nanofibers showed that nanofibers with higher shell flow ratio released BMP2, IGF1, and BSA more slowly in 3 days and in a more sustained manner up to 28 days of release [87]. Similar studies evaluated the release of BSA and NGF [9], BSA and tetrapeptide val-gal-pro-gly [88], and antibiotics (vancomycin and ceftazidime) and BMP2 from core-shell nanofibers [89].…”
Section: Delivery Of Multiple Drug and Biomolecules From Core-shell Nmentioning
confidence: 83%
“…Finally, it was concluded that NGF released from the core-shell nanofibers retained bioactivity up to 10 days [9]. Core-shell nanofibers were designed by incorporating BMP2 and insulin-like growth factor 1 (IGF1) at different flow ratio [87]. BSA was a stabilizer in the system.…”
Section: Delivery Of Multiple Drug and Biomolecules From Core-shell Nmentioning
confidence: 99%
“…The nano-scale structure of the fibers is similar to the natural extracellular matrix. It has a high surface-to-volume ratio and could improve cell attachment 24 , 42 . Simultaneously, fibers cross-formed pore structures that allowed sufficient permeability to nutrients and gas exchange for the regenerated tissue 43 .…”
Section: Discussionmentioning
confidence: 99%
“…The bone marrow mesenchymal stem cells were isolated from Sprague–Dawley (SD) rats (female, age 3–4 weeks, 80–100 g, from the Experimental Animal Center of Lanzhou University). The primary BMMSCs were isolated and cultured according to a previously reported protocol with minor modifications 24 . Cells were incubated in low-glucose Dulbecco’s modified Eagle’s medium (L-DMEM) (HyClone, USA) containing 10% fetal bovine serum (FBS) and 100 U/mL penicillin/streptomycin (Gibco) at 37 °C under 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The original TGF-b3 powder was reconstituted at 20 lg/ ml in sterile 4 mM hydrochloric acid containing 1 mg/ml BSA. Coaxial electrospinning was performed as previously described [15]. Briefly, PLCL-collagen and TGF-b3 solutions were delivered into the coaxial outer and inner needles, respectively, before electrospinning.…”
Section: Scaffold Fabricationmentioning
confidence: 99%